(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the current status of selected anxiety disorders among individuals aged 18 to 60 in Thai Binh province during the period 2024-2025. Subjects and methods: A cross-sectional study was designed to investigate the current status of selected anxiety disorders among individuals aged 18-60. Results: Anxiety was prevalent among individuals aged 18-60, with an overall rate of 14.4%. The highest prevalence of anxiety disorders was observed in the 51-60 age group (29.4%), with females accounting for 83.3% of the cases. Widowed individuals represented 65.9% of those affected, and the prevalence was higher among those with lower educational levels (illiterate: 33.3%; lower secondary education: 24%). Generalized anxiety disorder had the highest prevalence (10.6%), followed by mixed anxiety-depressive disorder and panic disorder. Other anxiety disorders accounted for lower proportions. Conclusion: The prevalence of anxiety disorders was higher among individuals aged 51-60, females, those who were widowed, separated, or divorced, individuals with low educational attainment.